The Expression of Sphingosine-1 Phosphate Receptor-1 in Chronic Lymphocytic Leukemia Cells Is Impaired by Tumor Microenvironmental Signals and Enhanced by Piceatannol and R406 - Borge, Mercedes (2014)
Chronic lymphocytic leukemia (CLL) is characterized by the progressive accumulation of clonal B lymphocytes. Proliferation occurs in lymphoid tissues upon interaction of leukemic cells with a supportive microenvironment. Therefore, the mobilization of tissue-resident CLL cells into the circulation is a useful therapeutic strategy to minimize the reservoir of tumor cells within survival niches. Because the exit of normal lymphocytes from lymphoid tissues depends on the presence of sphingosine-1 phosphate (S1P) and the regulated expression of S1P receptor-1 (S1PR1), we investigated whether the expression and function of S1PR1 can be modulated by key microenvironment signals. We found that activation of CLLcells with CXCL12, fibroblast CD40L(+), BCR cross-linking, or autologous nurse-like cells reduces their S1PR1 expression and the migratory response toward S1P. Moreover, we found that S1PR1 expression was reduced in the proliferative/activated subset of leukemic cells compared with the quiescent subset from the same patient. Similarly, bone marrow-resident CLL cells expressing high levels of the activation marker CD38 showed a lower expression of S1PR1 compared with CD38(low) counterparts. Finally, given that treatment with BCR-associated kinase inhibitors induces a transient redistribution of leukemic cells from lymphoid tissues to circulation, we studied the effect of the Syk inhibitors piceatannol and R406 on S1PR1 expression and function. We found that they enhance S1PR1 expression in CLL cells and their migratory response toward S1P. Based on our results, we suggest that the regulated expression of S1PR1 might modulate the egress of the leukemic clone from lymphoid tissues.